Learning Latinidad: The role of a Latino cultural center service-learning course in Latino identity inquiry and sociopolitical capacity. Issue 2 (2nd April 2020) - Castillo-Montoya, Milagros; Verduzco Reyes, Daisy
ABSTRACT: College culture centers are safe havens for underrepresented students, yet we know little about them. Through a survey with open- and closed-ended questions, this exploratory study examined the experiences and learning of 9 out of 11 college students who completed an academic course offered through a Latino Cultural Center (LCC). Through analysis of open-ended responses, we found that these students (1) engaged in Latino identity inquiry; (2) developed critical consciousness; (3) developed sociopolitical capacity; and (4) viewed Latino faculty as valuable to their learning. Findings have implications for conceptualizing Latino identity inquiry and framing concepts for future LCC research.